Maternal attitudes and home-based interventions for enhancing social, attention, and language skills in children with autism in Diwaniyah, Iraq - Al-Hamza Marhoon, Aqeel Abd; Obaid, Khamees Bandar (Frontiers in Psychiatry, 2025)
BackgroundAutism Spectrum Disorder (ASD) presents significant developmental challenges, particularly in low-resource settings. Maternal attitudes and engagement in home-based interventions are critical for supporting children’s social, attention, and language development.AimsTo assess maternal attitudes toward children with ASD and evaluate the implementation of home-based interventions targeting social, attention, and language skills in Diwaniyah, Iraq.MethodsA descriptive, cross-sectional study was conducted between April and August 2025, involving a census sample of 205 mothers of children with ASD from three autism centers in Diwaniyah. Data were collected through structured face-to-face interviews using a validated questionnaire. Statistical analyses were performed using SPSS version 25, with descriptive statistics and Chi-square tests applied to examine the data.ResultsThe majority of mothers (79.0%) exhibited positive attitudes toward their children with ASD. Positive maternal attitudes were significantly associated with higher education, urban residence, sufficient income, attendance at educational sessions, and absence of family mental illness (p < 0.05). Home-based intervention implementation was high in most domains: 67.3% for social skills, 88.8% for attention, and 67.8% for language. A statistically significant association was found between positive maternal attitudes and the use of home-based interventions targeting social skills (P value = 0.001), but not for attention or language interventions (P values > 0.05). After adjusting for potential confounders, the results show that maternal attitudes were significantly associated only with the likelihood of using home-based interventions within the social domain (adjusted odds ratio = 1.021; 95% CI: 0.208-5.010; p = 0.001).ConclusionMaternal attitudes significantly influence the implementation of home-based social skill interventions in children with ASD. Strengthening caregiver training and psychosocial support, particularly in underserved areas, is essential to enhance home-based developmental outcomes in low-resource contexts like Diwaniyah.